2006
DOI: 10.1002/cbf.1257
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of protein oxidation and lipid peroxidation in patients with rheumatoid arthritis

Abstract: We aimed to determine the importance of neutrophil activation and the source of oxidative stress in the pathogenesis of rheumatoid arthritis (RA) by quantification of advanced oxidation protein products (AOPP) and total thiol levels as markers of oxidative protein damage, malondialdehyde (MDA) levels as a marker of lipid peroxidation and myeloperoxidase (MPO) activity as a marker of neutrophil activation in patients with RA. Fifty-seven rheumatoid arthritis patients were included in the study and sub-grouped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 31 publications
4
62
1
Order By: Relevance
“…We used the substances reacting with thiobarbituric acid measured in plasma at 535nm (Brown & Kelly, 1996). Clinical studies have shown increased plasmatic levels of MDA in patients with RA (Baskol et al, 2005(Baskol et al, , 2006Sarban et al, 2005). The level of MDA in the plasma of arthritic animals was also elevated (Bauerova et al, 2008bHe et al, 2006;Sotnikova et al, 2009;Strosova et al, 2008Strosova et al, , 2009Tastekin et al, 2007).…”
Section: Adjuvant Arthritis: An Animal Model For Preclinical Evaluatimentioning
confidence: 99%
“…We used the substances reacting with thiobarbituric acid measured in plasma at 535nm (Brown & Kelly, 1996). Clinical studies have shown increased plasmatic levels of MDA in patients with RA (Baskol et al, 2005(Baskol et al, , 2006Sarban et al, 2005). The level of MDA in the plasma of arthritic animals was also elevated (Bauerova et al, 2008bHe et al, 2006;Sotnikova et al, 2009;Strosova et al, 2008Strosova et al, , 2009Tastekin et al, 2007).…”
Section: Adjuvant Arthritis: An Animal Model For Preclinical Evaluatimentioning
confidence: 99%
“…1,7 IMA was first described as a marker of myocardial ischemia, but lately it is being intensively investigated in other disorders, including diabetes, and in other conditions associated with oxidative stress. 8,9 Increased AOPP and IMA formation are observed in different diseases and have been recognized as early markers and/or prognostic factors for numerous pathological conditions, such as acute coronary syndrome, systemic sclerosis, rheuamthoid arthritis, trauma, pulmonary embolism [10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Reactive oxidants are generated as a consequence of an "oxidative burst" of phagocytic cells (e.g., macrophages and neutrophils) activated by T. cruzi infection (8). NADPH oxidase, activated in all phagocytic cells, produces superoxide (O 2 ⅐ Ϫ ) (1,11). Endothelial activation of xanthine oxidase (XOD) in response to T. cruzi infection also results in increased O 2 ⅐ Ϫ production via oxidation of hypoxanthine to xanthine and uric acid (3,17).…”
mentioning
confidence: 99%
“…⅐ NO, produced in abundance by iNOS, directly reacts with O 2 ⅐ Ϫ to form peroxynitrite (ONOO Ϫ ) and peroxynitrous acid (ONOOH), which have been shown to kill T. cruzi (36). Alternatively, nitrite (NO 2 Ϫ ), a major product derived from ⅐ NO, may be oxidized by MPO to nitrogen dioxide (NO 2 ⅐ ), which may further react with HOCl to form the highly reactive compound nitryl chloride (NO 2 Cl) (5).…”
mentioning
confidence: 99%